Increased synthesis of hyaluronic acid by enhanced penetration of CTP‐EGF recombinant in human keratinocytes. (20th January 2019) - Jeon, Yoon‐Jae; Kim, Young‐Hoon; Jeon, Ye Ji; Lee, Wan‐Won; Bae, Il Geun; Yi, Ki Wan; Hong, Seung Ho
Summary: Background: Epidermal growth factor (EGF) plays an important role in regeneration and proliferation of skin cells. It synthesizes fibrous proteins, such as collagen, and induces the proliferation of keratinocytes and fibroblasts. It can also induce hyaluronic acid synthesis, which subsequently leads to improved skin elasticity, wrinkle improvement, and moisturizing effects. Thus, the EGF is an attractive cosmetic additive for skin care. Objectives: We tested the use of cytoplasmic transduction peptide (CTP) as a delivery peptide for EGF into skin cells. Additionally, we characterized the skin permeability of CTP‐EGF for its potential use in skin antiaging and antiwrinkle cosmetics. Methods: Skin penetration by recombinant CTP‐EGF protein was confirmed using fluorescent imaging techniques. The ability to synthesize hyaluronic acid was confirmed by immunoblotting and ELISA. Results: CTP‐EGF displayed cell membrane permeability and could penetrate skin cells. Treatment with CTP‐EGF increased collagen protein formation, which is a major regulator of skin elasticity. Further, CTP‐EGF treatment led to increased expression of HAS3 enzyme and subsequently boosted hyaluronic acid synthesis. The CTP‐EGF also performed better than natural EGF in wound healing assays. Conclusions: CTP‐EGF has a superior ability, compared with natural EGF, to permeate skin and induce hyaluronic acid synthesis and collagen formation. Thus, it has great potential to be used in cosmetics and therapeutic agents to improve wrinkles and health of the skin.